Religious Self-Identification and Culture—About the Role of Religiosity in Cultural Participation - Lipnicka, Magdalena (Religions, 2021)
Culture has its source and anchoring in religion, but the presence of religious values in social life takes place in terms of culture and through culture. Religiosity plays a key role in defining the boundaries of cultural differences, and this paper raises questions as to the extent, ways and environments where religiosity may influence active cultural participation. The research paper attempts to identify the impact of religiosity on such activities. This involves determining which dimensions of religiosity should be distinguished and are most relevant for cultural participation in Poland. The study showed that religiosity influences cultural participation, but ambiguously. Religious self-identification and spiritual self-identification turned out to be the most significant factors. Religiosity is relevant for cultural participation, but mainly when it is a significant element of individual identity.